Chosen Aspects and Specifics of the Formation of Civil Society and Political Party Spirit within the Habsburg Monarchy of the Second Half of the 19th Century with Regard to Moravia - Krakora, Pavel (Civilia, 2019)
The text focuses on the formation of civil society and political party spirit in the framework of the Habsburg monarchy in the second half of the 19th and early 20th century. In order to better understand the basic and fundamental contexts, a region of Moravia was chosen to illustrate the development of society and political parties. Moravia was one of the most developed areas within the Habsburg monarchy - politically, economically and socially (rich social life, a developed network of schools, cultural organizations and others). Another important factor in this respect was the relative proximity of Vienna, the capital city of the monarchy, and Prague, the centre of the Czech lands on the other. Immediately after the restoration of the constitution in 1861, there was an expansion of social life in Moravia, which was closely linked to the emergence of political parties as a manifestation of the gradual emancipation of civil society. From today's perspective, this process showed some deficits, such as the honorary nature of political parties or limited voting rights. However, in the contemporary context we can speak of a fundamental divide that initiated the gradual transformation of the original patrimonial (feudal) society into a modern civil society with all its customs and institutes. In the conditions of Moravia, which was part of not only the Habsburg monarchy, but also the narrower framework of the Czech lands, the process of forming civil society corresponded to the process of forming the modern Czech nation and the Czech national consciousness. However, this also contributed to the rise of nationalism reflected in the Czech-German antagonism, which, in addition to the war events of 1914-1918, became one of the important factors of the Austro-Hungarian monarchy collapse.
Keywords: Civil society; Political parties; History; Education; Habsburg Monarchy; Moravia